PREFERENSI KOMUNIKASI PEMASARAN TERPADU PERGURUAN TINGGI DI SURABAYA PADA ERA POSMODEREN - Hilda Yunita Wono; Imanuel Deny Krisna Aji (Universitas Bunda Mulia, 2020)
This study aims to determine the activities of Integrated Marketing Communication (IMC) which is the preference of students at private universities X in Surabaya. This research is a quantitative type of research using the slovin method and stratified random sampling combined with purposive sampling as a sampling method. Existing data is processed using SPSS Statistics so that the data is presented in tabular form as data analysis. The results of this study were to find several IMC activities that were considered the most interesting by these college students, starting from the most popular ones namely sales promotion (42%) and followed by personal sales, and advertising. In this study also known some IMC activities that are considered unattractive or even unknown by students in this tertiary institution starting from those considered unattractive or unknown such as events and experiences (31%), then following with direct marketing activities, and finally is an advertisement where some unknown or uninterested students are found.